Network Pharmacology Approach to Unveiling the Mechanism of Wolfberry Mulberry Raspberry Decoction in the Treatment of Sepsis-Induced Myocardial Dysfunction - Zhang Q; Wen L; Li J; Liu P; Sun X; Liu Q; Chen X; Zhang Y (Drug Design, Development and Therapy, 2025)
Qingqiong Zhang,1,* Lianbin Wen,1,* Junxian Li,2 Peng Liu,1 Xuechun Sun,1 Qingsong Liu,2,3 Xiaomei Chen,4 Yanfang Zhang5 1Department of Geriatric Cardiology, Sichuan Provincial People’s Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, Sichuan, 610072, People’s Republic of China; 2Department of Traditional Chinese Medicine, Sichuan Provincial People’s Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, Sichuan, 610072, People’s Republic of China; 3School of Acu-Mox and Tuina, Chengdu University of Traditional Chinese Medicine, Chengdu, People’s Republic of China; 4Department of Geriatrics, Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan, 610075, People’s Republic of China; 5Department of Public Health Center, People’s Hospital of Ningxia Hui Autonomous Region, Ningxia Medical University, Yinchuan, Ningxia Hui Autonomous Region, 750002, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yanfang Zhang, Department of Public Health Center, People’s Hospital of Ningxia Hui Autonomous Region, Ningxia Medical University, Yinchuan, Ningxia Hui Autonomous Region, 750002, People’s Republic of China, Email zhangyanfang@nxrmyy.com Xiaomei Chen, Department of Geriatrics, Hospital of Chengdu University of Traditional Chinese Medicine, 39 Shi-Er-Qiao Road, Jinniu District, Chengdu, Sichuan, 610072, People’s Republic of China, Tel +86-18080407013, Email 3612556@qq.comObjective: To investigate the mechanisms by which the Wolfberry Mulberry Raspberry Decoction (WMRD) affects Sepsis-Induced Myocardial Dysfunction (SIMD) using network pharmacology and experimental validation.Methods: We explored the TCM Systems Pharmacology Database to gather biological data for WMRD compounds. The GeneCards, PharmGkb, Therapeutic Target Database (TTD), and Online Mendelian Inheritance in Man (OMIM) databases were utilized to identify target proteins associated with SIMD. Overlapping elements between SIMD and drug targets were analyzed. This data was integrated into the STRING platform to visualize protein interactions. Cytoscape software was then used to construct a network diagram illustrating relationships between drug components and their corresponding targets. Gene Ontology enrichment and Kyoto Encyclopedia of Genes and Genomes pathways analyses were conducted using a database for annotation and visualization. Predictive pathways were validated through experimental studies on cellular and animal models.Results: Network pharmacology analysis identified 58 active compounds of WMRD and revealed that WMRD partially ameliorated SIMD by modulating apoptosis, TNF signaling pathway and IL-17 signaling pathway. Quercetin, one of the main components of WMRD, suppresses apoptosis and oxidative stress in H9C2 cell via regulating the MMP9, TNF-α, IL-1β and BCL/BAX axis. Quercetin increased BCL-2 expression and decreased MMP9, TNF-α, IL-1β, Bax, and Caspase-3 protein expression in H9C2 cells treated with LPS. Moreover, Quercetin attenuated LPS-Induced myocardial injury and apoptosis in SIMD mice model. Therefore, this study suggests that Wolfberry Mulberry Raspberry decoction may be a potential drug for the treatment of septic myocardial injury, in which Quercetin may play an important role.Conclusion: Quercetin, a key component of WMRD, suppressed H9C2 cell apoptosis by dysregulating MMP9, TNF-α, IL-1β, and BCL/BAX axis, highlighting its therapeutic potential in SIMD. Keywords: sepsis-induced myocardial dysfunction, H9C2 cells, quercetin, network pharmacology, wolfberry mulberry raspberry decoction